Keragaman Kedalaman Kemiskinan Rumah Tangga menurut Tipe Wilayah dan Karakteristik Sosial Ekonomi Rumah Tangga Provinsi Jambi - Suardani, Ni Kadek; Kadir, Kadir (UI Scholars Hub, 2024)
Abstract. Ideally, government would be more comprehensive in looking at poverty alleviation issues; not only on the indicator of poverty incidence. They needs analysis related to poverty gap, to find out how poor are the poor, so that it becomes input for more effective poverty reduction. This research aims to analyze the diversity of poverty gap at the household level in Jambi Province according to regional type and socio-economic characteristics. Poverty gap is expressed as the gap between the per capita expenditure of poor households and the Poverty Line (PL). Using Susenas data for 2020-2022, this research found that half of poor households had a gap of around 11-15% of PL and few of them were above 50%. This means that the challenge of poverty in Jambi Province is actually greater in handling poor households whose existence is not too far from PL. The results of the Mann-Whitney test found significant differences in gaps according to a number of household characteristics, but differed between regions. The implication is that the Jambi Provincial government, in its efforts to accelerate poverty reduction, can focus more on urban areas by paying attention to the characteristics of poor households which are closely related to variations in the poverty gap.